Doing business internationally : the cross-cultural challenges. - MultiMedia Inc.; Princeton Training Press; Training Management Corporation ([Princeton, NJ] : MultiMedia Inc., 1992)
Provides a solid foundation on which participants can build skills needed to conduct business in a variety of cultural settings and thereby meet the global business challenge.
Support materials by Princeton Training Press, a division of Training Management Corporation.
Keywords: International business enterprises -- Management